(untitled) (MAUSAM, 2002)
A comprehensive analysis of eleven break monsoon situations that occurred during the period 1987 to 1997 have been attempted in the study. The various features like daily rainfall departures, wind anomalies and the satellite derived Outgoing Long wave Radiation (OLR) associated with the commencement/cessation of the break monsoon condition are studied with a view to identifying the precursors associate the break situation. The results reveal that there is progressive decrease of below normal rainfall departures 5 days prior to the actual break day in the latitude belts south of 20° N. During the period of the revival of the monsoon, the time section of the daily rainfall departures shows that the daily rainfall departure first starts becoming above normal in the southern most latitudinal belt 5° N to 10°N from the second day onwards after the cessation of the break. Similarly, the easterly anomalies in the zonal wind are first noticed in the southern latitude even 5 days prior to the starting of the break in the lower and middle troposphere. The maximum easterly anomalies in the lower and the middle troposphere move northwards upto 20° N. The composite latitudinal time section of OLR anomaly show a large area of negative OLR anomaly extending from 20°S to 10°N. The area is defined as the Southern. Hemispheric Convective Zone ( SHCZ). The negative OLR anomaly (10 Wm-2 is noticed around 5° S to 0° N. It increases to 20 Wm-2 on the second day of the break on the same latitudinal belt. The daily OLR anomaly pattern shows that the area of the negative OLR anomaly around the equatorial region increases with the approach of a break epoch. The forecasting aspects of the commencement / cessation of the break have been also discussed.